Penerapan Terapi Cairan Nacl 0,9% pada Ulkus Diabetikum dengan Masalah Keperawatan Risiko Infeksi di Ruang Lavender Atas RSUD Kardinah Kota Tegal - Muhamad Pujianto; Ahmad Syaripudin; Lily Wahyuni R. (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Diabetes Mellitus is a chronic metabolic disorder characterized by hyperglycemia due to defects in insulin secretion, insulin action, or both. WHO reported in 2024 that in Indonesia, approximately 75-80% of diabetes hospitalizations are caused by foot complications, with 30-40% involving diabetic ulcer cases that carry a high risk of infection. To analyze the application of wound care using 0.9% NaCl solution in diabetic ulcer patients with a nursing problem of infection risk in the Upper Lavender Room of Kardinah Regional Hospital, Tegal City. Descriptive quantitative research utilizing a nursing care case study approach. The instruments included assessment forms, medical records, and the Standard Operating Procedure (SOP) for wound care using 0.9% NaCl solution. There was a significant decrease in the risk of infection after the patient received wound care interventions using 0.9% NaCl solution 3 times over 4 days, characterized by a reduction in clinical signs of infection such as redness, odor, and wound exudate. The application of wound care using 0.9% NaCl solution is proven effective in reducing the risk of infection and stimulating new tissue growth in diabetic ulcer patients, making it highly viable as a routine nursing procedure.